The impacts of infrastructure in development: A selective survey - Yasuyuki Sawada (Asian Development Bank Institute (ADBI), 2015)
Development economists have considered physical infrastructure to be a precondition for industrialization and economic development. Yet, two issues remain to be addressed in the literature. First, while proper identification of the causal effectiveness of infrastructure in reducing poverty is important, experimental evaluation, such as randomized control trials (RCT)-based evaluation, is difficult in the context of large-scale infrastructure. Second, while micro studies so far have focused on the nexus between infrastructure and certain types of poverty outcomes such as income, poverty, health, education, and other individual socio-economic outcomes, to better interpret a wide variety of micro-level infrastructure evaluation results using either experimental or non-experimental methods, the role of infrastructure should be placed in a broader context. To bridge these gaps, we augment the existing review articles on the same topic, such as Estache (2010), Hansen, Andersen, and White, (2012), and World Bank (2012) by addressing these two remaining issues. First, while forming a counterfactual is often difficult for impact evaluation of infrastructure, engineering constraints beyond human manipulation can allow people to adopt quasi-experimental methods of impact evaluation. Second, evaluators can adopt, for example, a hybrid method of natural and artefactual field experiments to elicit the role of infrastructure in facilitating the complementarity of the market, state, and community mechanisms.
Keywords: C93; H54; O1; O18; 330; physical infrastructure; economic infrastructure; social infrastructure; poverty reduction